СURRENT TECHNOLOGIES OF STAFF TRAINING IN HOTEL BUSINESS - O. S. Suvalov; T. V. Suvalova (Вестник университета)
The aim of the study is to analyse the effectiveness of the applied technologies and teaching methods in the field of hospitality. The nature and relevance of training programs have been considered in the article. The necessity and advantages of investments in employee development have been substantiated. The specificity of the hotel industry business has been noted. The role of uniform requirements for professional knowledge and skills of qualified specialists has been emphasized. The advantages of internal corporate training in thecomparison to external have been revealed. The process of introducing training technology in the hotel complex has been considered. The stages of pre-training diagnostics, development of training programs, training and post-training support have been highlighted. Training methods depending on the type of employees have been described. The assessment of the effectiveness of personnel training according to the Kirpatrick model has been reviewed. The role of training in the successful business of companies has been argued.